Use of single and double trunk in training of Concord Seedless and Superior Seedless grapevines - Girgis, V.H.; Bondok, Sawsan A.; EI-Shenawy, S.I. (2007)
A field experiment was conducted during 2004 and 2005 growing seasons In a private farm at Wadi EI-Natroun, Sehera Governorate, Egypt to study the effect of using single and double trunk on vine yield and quality of Concord and Superior Seedless grapes under drip Irrigation system and sandy soli conditions of Nubaria region. A separate trial was performed for each cultivar. The results showed superiority of using the double trunk system over the single trunk since It had higher j) percentages of bud burst and fruitful buds per vine, bud fertility and higher values of old wood size. There is a significant yield Increase, in favour of the double trunk (OT) as compared to that. of the single trunk (ST). Also, average weight prunings revealed significant Increase for the OT system over that of the ST system. Both treatments had no significant effect on physical and chemical fruit parameters. The results were nearly similar to those of both cultivars with regard to these estimates. From this study it could be concluded that, for high production of Concord and Superior grapevines in the sandy soil of Nubaria region the use of double trunk in the training system is recommended.
Includes references.
Summary in Arabic.
1
Keywords: Grapes -- Breeding; Grapes -- Egypt